CVD growth of the nanostructured Ni3S2 thin films as efficient electrocatalyst for hydrogen evolution reaction. (June 2021) - Kajbafvala, Marzieh; Moradlou, Omran; Moshfegh, Alireza Z.
Abstract: The development of low cost and earth abundant electrocatalyst with high performance and desirable stability for hydrogen evolution reaction (HER) is an important issue in energy applications. Nickel sulfide thin films (NiS x ) are formed on conductive nickel foam substrates via chemical vapor deposition (CVD) at 300 °C under low pressure condition. A single phase of Ni3 S2 was produced by controlling the ratio of precursors. X-ray diffraction (XRD), field emission scanning electron spectroscopy (FESEM), X-ray photoelectron spectroscopy (XPS) and electrochemical measurements were conducted to characterize and compare properties of the samples. According to XRD and XPS data analysis, the growth of single phase and surface chemical composition of the Ni3 S2 was confirmed on the substrate. The results showed that by changing the molar ratio of S/Ni, nickel sulfides are crystalized in different phases including Ni3 S4, NiS and Ni3 S2 . Electrochemical measurements conducted for HER activity showed that the Ni3 S2 phase has the lowest overpotential, 116 mV vs. RHE, in comparison with two other phases (NiS and Ni3 S4 ). Ni3 S2 possesses many accessible active sites with a relative electrochemical surface area of about 83. Finally, the Tafel slopes for Ni3 S2, NiS and Ni3 S4 were obtained to be 96, 154 and 197 mV/dec, respectively. Highlights: Chemical vapor deposition (CVD) is used to grow single phase Ni3 S2 thin films by controlling the ratio of precursors. XRD, FESEM, EDX, XPS and electrochemical measurements are applied to determine properties of the deposited samples. The measured overpotential for the Ni3 S2 thin film is achieved at 116 mV versus reversible hydrogen electrode, that is the lowest among other phases. Tafel slopes for Ni3 S2, NiS and Ni3 S4 are obtained at 96, 154 and 197 mV/dec, respectively.